PENGARUH BAHAN PENGISI ABU LIMBAH GIPSUM PADA CAMPURAN BETON ASPAL MODIFIKASI LATEKS MENGGUNAKAN METODE UJI MARSHALL - Yosea Managam Sianturi; Risma Masniari Simanjuntak; Setiyadi (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2022)
Rock ash, limestone powder, and Portland cement are joint fillers used in flexible pavements, but their manufacturing is limited, necessitating alternate materials. This research aimed to determine the use of gypsum waste ash as a filler in asphalt concrete utilizing the Marshall process. Filler is an essential ingredient, particularly in asphalt-concrete combinations. The use of latex-modified bitumen at 7% of the optimum asphalt content of 6% and a variation of 5%, 6%, 7%, and 8% gypsum waste ash filler with rock ash filler is expected to increase the stability value while decreasing the degree of stability and flexibility degradation due to re-soaking specimens by wet dry process. Except for the melting point, Marshall and volumetric tests on specimens without immersion with a gypsum ash level of 6.5% revealed that most specimens met the Highways 2010 revision 2 standards. The test results at 6.5% gypsum waste ash filler content also indicated a rise in the stability value and Marshall Quotient (MQ), indicating that the test item is becoming stiffer. The test findings on re-soaked test specimens showed the slightest loss in stability values at 6.5% gypsum ash filler level, which was 8%. The loss in stability in the soaked mixture without gypsum ash could reach 36.18%. The Marshall Quotient value from the soaking data was 180.41 kg/mm, compared to 182.59 kg/mm for the mixture without gypsum ash. According to this, gypsum waste ash at a content of 6.5% is a mixture that can be recommended as a flexible road paving material.